Removal of Water in Liquid Fuel with a Super Absorbent Copolymer - Ismail, O.; Beyribey, B.; Turhan, K. (TAYLOR & FRANCIS INC, 2011)
In this study, acrylic acid-based super absorbent copolymer was synthesized to remove existent water in liquid fuel by an inverse suspension polymerization technique. The inverse suspension polymerization was accomplished with the use of aqueous solutions of partly neutralized acrylic acid with a predetermined cross linker agent/monomer ratio in cyclohexan. Sorbitan monostearate was use to obtain the suspension. NaOH is used for neutralization of the acrylic acid. Ethylene glycol dimethacrylate and potassium persulfate are also used respectively as a crosslinker agent and an initiator. The copolymer was characterized by IR spectroscopy and SEM micrographs. The water absorption capacities and rates of the copolymer in tap water and the mixture of water-liquid fuel were determined. The water absorption capacity of 1 g of copolymer in tap water and in the mixture of water-liquid fuel was respectively obtained as 208 +/- 0.22 and 207.5 +/- 0.06 g of water. The Karl Fisher method was used for determination of residual water in liquid fuel, and 420 ppm (desired amount) of residual water in liquid fuel was calculated.
Keywords: absorption; acrylic acid; copolymer; fuel; removal; SUPERABSORBENT POLYMERIC MATERIALS; ACRYLIC-BASED SUPERABSORBENTS; INVERSE SUSPENSION; Energy & Fuels; Engineering; Environmental Sciences & Ecology